PENGARUH KOMPETENSI, TINGKAT PENDIDIKAN AUDITOR DAN TIME BUDGET PRESSURE TERHADAP KUALITAS HASIL AUDIT - Robertus Aryo Kusumo Widodo; Bambang Agus Pramuka; Eliada Herwiyanti (Universitas Katolik Indonesia Atma Jaya, 2016)
This research aims to examine the effect of competence, education level ofthe auditor, and time budget pressure on audit results quality.This research uses agency theory and expectancy theory. The research population was BPKP auditor in West Nusa Tenggara province. The sampling method was convenience sampling. The data collection was obtained by questionnaire.The data collection was obtained by questionnaire. The research results show that there is an influence from competence and auditor’s level of education on audit results quality, while there is no effect of time budget pressure on audit results quality.The coefficient of determination shows that audit results quality can be explained by 63.9% based on variations of the independent variables in the research, and 36.1% is not explained by the regression model and explained by other causes outside the regression model.